PCR in the differential diagnosis of Tuberculosis: A comparative study - 2, Parthiban K3, Senthil Kumar K4 and Thirumurugan R2*, Sheeba Christina A1, Vignesh V2, Kanipandian N2, Vasuki B2, Nishanthini A (International Multidisciplinary Research Journal, 2011)
<div style="border-bottom: windowtext 1pt solid; border-left: medium none; padding-bottom: 1pt; padding-left: 0in; padding-right: 0in; margin-left: 34pt; border-top: medium none; margin-right: 34pt; border-right: medium none; padding-top: 0in; mso-element: para-border-div; mso-border-bottom-alt: solid windowtext .5pt;"> This study is to assess prospectively the performance of PCR in the diagnosis of Tuberculosis. The repetitive sequence IS6110 is used as a target for PCR. A total of five samples were analyzed all of which were found to be PCR positive. The results were compared with AFB staining, culture on Lowenstein Jensen (LJ) medium and Enzyme Linked Immunosorbant Assay (ELISA). PCR was found to be sensitive and specific and provides a definitive diagnosis of TB. Hence it is an effective tool for TB diagnosis.